2017
DOI: 10.1136/thoraxjnl-2017-210010
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils drive alveolar macrophage IL-1β release during respiratory viral infection

Abstract: BackgroundAlveolar macrophages are sentinels of the airways that must exhibit immune restraint to innocuous antigens but elicit a robust inflammatory response to pathogenic threats. How distinction between these dichotomous functions is controlled is poorly defined.Neutrophils are the first responders to infection, and we hypothesised that they may free alveolar macrophages from their hyporesponsive state, promoting their activation. Activation of the inflammasome and interleukin (IL)-1β release is a key early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 45 publications
2
63
0
1
Order By: Relevance
“…Antibody-mediated depletion of neutrophils specifically reduced the amount of influenza-induced IL-1β but not IL-6 or tumour necrosis factor-alpha, suggesting that the neutrophils were directly responsible for this increase in IL-1β 8. Moreover, neutrophil depletion only reduced viral-induced, not bacterial-induced, release of IL-1β.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Antibody-mediated depletion of neutrophils specifically reduced the amount of influenza-induced IL-1β but not IL-6 or tumour necrosis factor-alpha, suggesting that the neutrophils were directly responsible for this increase in IL-1β 8. Moreover, neutrophil depletion only reduced viral-induced, not bacterial-induced, release of IL-1β.…”
mentioning
confidence: 88%
“…Pneumonias are primarily associated with massive neutrophil influx into the lung leading to compromised gas exchange but there are conflicting reports as to whether the role of the neutrophil in viral infections is protective or pathological 7. The study by Peiró et al 8 has provided further insight into the complex interplay between macrophages and neutrophils in a mouse model of influenza infection.…”
mentioning
confidence: 99%
“…60,61 Neutrophils are also crucial for the induction of IL-1β produced by macrophages. 62 Recent pathway-analysis studies have also identified upregulation in several neutrophil-related pathways to be associated with influenza disease severity. 63,64 Alveolar macrophages are resident cells in lung and are the major producers of type I IFN upon influenza infection.…”
Section: Innate Immune Cells Ards and Cytokine Stormsmentioning
confidence: 99%
“…Furthermore, these increased neutrophil populations exhibited impaired antimicrobial activity compared to single-infected equivalents, and the increased presence of these cells appears to drive pathology to influenza. 26 Such observations suggest excessive neutrophil recruitment as a major factor in secondary bacterial mortality. A further study demonstrated that influenza infection appears to drive massive alveolar macrophage depletion (in some cases up to 90% depletion); after which secondary bacterial pneumonia occurs.…”
Section: Influenza Infection Leads To Bacterial Invasion Of Parenchymmentioning
confidence: 99%